Measuring metabolic energy expenditure with short duration walking tests for individuals with lower limb amputation - Andrea J. Ikeda; Jessica A. Smit; Ann M. Simon; Shawana J. Anarwala; Levi J. Hargrove (PLoS ONE, 2025)
Introduction Metabolic assessment of prosthetic gait is useful when comparing devices, interventions, or populations. However, the standard requirement to walk continuously for six minutes or more to reach steady state (SS) is difficult for many individuals with lower limb amputation. Our goal was to assess the concurrent validity of metabolic outcomes from shorter duration walking tests with those from the standard six-minute walk, in persons with transfemoral or transtibial amputation. Methods Thirty participants (amputation: 10 transfemoral, 10 transtibial, 10 none) performed three walking tests while data were collected with a wearable metabolic system: 1) two-minute treadmill walk plus 10-minute recovery, 2) six-minute treadmill walk, and 3) overground two-minute walk test (2MWT). Three different analyses were performed to correlate SS metabolic outcomes from minutes 5-6 of the six-minute treadmill walk with: 1) total oxygen uptake from the two-minute treadmill walk, incorporating excess post-exercise oxygen consumption (EPOC), 2) minute interval outcomes from minutes 1-4 of the six-minute treadmill walk, and 3) outcomes during minutes 1 and 2 of the 2MWT. Results Strong correlations were found between total oxygen uptake of the two-minute treadmill walk plus EPOC and SS oxygen uptake (Pearson r 0.86 to 0.94). Likewise, there were strong correlations between minute interval outcomes of minutes 2, 3, and 4 of the six-minute treadmill walk and SS outcomes (Pearson r 0.82 to > 0.99). Fewer significant correlations were observed when comparing 2MWT outcomes with SS outcomes (Pearson r 0.41 to 0.78). Conclusion Strong correlations between metabolic outcomes of shorter duration walking tests with SS outcomes suggest that treadmill walking tests as short as two minutes may be acceptable to compare energy expenditure between conditions in individuals with lower limb amputation for circumstances where longer duration tests would not be possible. Additionally, these shorter tests would be more similar to real-life activities and more accessible for those with lower limb amputation.